2001
DOI: 10.1002/1099-0690(200104)2001:8<1533::aid-ejoc1533>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Novel Ester-Linked Carbohydrate−Peptide Adducts: Effect of the Peptide Substituent on the Pathways of Intramolecular Reactions

Abstract: Carbohydrate−peptide conjugates in which D-glucose is linked through an ester linkage to the carboxy group of TyrPro (2), Tyr-Pro-Phe (5) or Tyr-Pro-Phe-Val (11), through the C6 hydroxy group of the sugar moiety were synthesized to examine the utility of this type of monosaccharide modification for peptide prodrugs. Evidence is provided that glycoconjugates 2, 5, and 11 easily undergo intramolecular chemical transformations, subsequent to attack of the free N-ter- [a]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 25 publications
(19 reference statements)
0
7
0
Order By: Relevance
“…However, the yields for carbohydrate−peptide conjugations are around 30% in the literature. 39 Bile acid glycoside, which has been identified in biological materials, has been synthesized as a mixture of α-and β-anomers (ratio of α:β = 1:3) in <30% yields, and it had to be purified via HPLC. 28 However, under our reaction conditions, the β-glycoside was obtained stereospecifically in 83% yield with no chromatography ( Table 2, entry 17).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…However, the yields for carbohydrate−peptide conjugations are around 30% in the literature. 39 Bile acid glycoside, which has been identified in biological materials, has been synthesized as a mixture of α-and β-anomers (ratio of α:β = 1:3) in <30% yields, and it had to be purified via HPLC. 28 However, under our reaction conditions, the β-glycoside was obtained stereospecifically in 83% yield with no chromatography ( Table 2, entry 17).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…It was also important to have known and wellcharacterized compounds to verify accuracy of estimation. Among many options, we have selected the 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 glycopeptides 1-4, 39 where the N-terminally protected dipeptide (Tyr-Pro, 1), tripeptides (Tyr-Pro-Phe, Blind extraction of four analytes from three mixtures in 2D NMR spectroscopy. Figures 1 to 4 and Table 1 demonstrate the experimental blind extraction of four pure-component COSY spectra from three mixtures by means of the described sparseness-based multivariate data analysis method.…”
Section: Setting Up An Experimentsmentioning
confidence: 99%
“…The study showed that the length of and the residues present in the peptide chain were the main factors controlling the intramolecular conversions. [18] These data have important implications for the development of glycopeptide based drugs and particularly for the development of prodrug strategies based on sugar conjugation.…”
Section: Saccharide Conjugationmentioning
confidence: 99%